Global realignment : the new world economic order : a thesis presented in total fulfilment of the requirements for the degree of Master of Business Studies in International Business at Massey University - Selvarajah, Christopher T (Massey University, 1996)
The purpose of this thesis is to describe the current state of the global environment in the study of international business. The thesis explains the shift in the economic forces away from multilateral arrangements to regional groupings. In particular the shift is towards regionalism, 'seen' as a medium measure, before 'globalism'. The study takes the view that the world is moving towards a tripolar global economic focus namely the European Union, the North American Free Trade Area and the Asia Pacific Economic Cooperation. The focus in the latter is on the development of the East Asian economies. The research was developed on the assumption that the concept of competition is changing from rivalry to collaboration and from independence to interdependence. This is true for nations as well as corporations. The research also attempts to describe the forces of change and the impact of change factors such as technology and information systems on the nature of competition. This research covers new developments in the study of the environments of international business. APEC and NAFTA are new institutions which have developed since 1989, and the European Union, whose history goes back to 1948, has in 1992 created a single Europe. These new developments require conceptualisation, academic focus and to be directed towards the teaching of international business. This research, it is hoped, does just that.
Keywords: International economic relations; World politics